2011
DOI: 10.1002/anie.201006636
|View full text |Cite
|
Sign up to set email alerts
|

13C Direct‐Detection Biomolecular NMR Spectroscopy in Living Cells

Abstract: A direct response: Exclusively heteronuclear 13C direct‐detection 2D NMR experiments are performed on 13C,15N‐enriched proteins in E. coli cells. Unfolded proteins or protein fragments provide well‐resolved carbonyl detection (see picture), whereas folded proteins or structured motifs do not give any detectable spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 33 publications
4
40
0
1
Order By: Relevance
“…5359 Recent reports, however, have disputed the longstanding notion that α-synuclein is a disordered monomer, and have instead suggested the formation of a helical tetramer under physiological conditions. 60,61 In either case, it is hoped that structural analyses of WT α-synuclein will provide insight into its function and also the onset and progression of neurodegenerative diseases.…”
Section: Historical Perspective and Biomedical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…5359 Recent reports, however, have disputed the longstanding notion that α-synuclein is a disordered monomer, and have instead suggested the formation of a helical tetramer under physiological conditions. 60,61 In either case, it is hoped that structural analyses of WT α-synuclein will provide insight into its function and also the onset and progression of neurodegenerative diseases.…”
Section: Historical Perspective and Biomedical Relevancementioning
confidence: 99%
“…11B) unambiguously confirmed that α-synuclein was a disordered monomer inside intact E. coli cells, which was consistent with previous studies. 59,120123 …”
Section: Disorder In the Court: Order?mentioning
confidence: 99%
“…Direct 13 C detection experiments are widely used to study IDPs due to the large dispersion of C′,N correlations in 2D CON spectra, and to the negligible sensitivity to solventexchange processes, which are quite pronounced in disordered regions. In addition, 13 C detection schemes were originally developed for the study of paramagnetic metalloproteins, to take advantage of the reduced sensitivity of heteronuclei to dipolar contributions and paramagnetic relaxation, which depend on the gyromagnetic ratio of the nuclear spins under observation.…”
Section: Figurementioning
confidence: 99%
“…但显微注射通常只适合于比 较大的细胞如卵母细胞(细胞直径约为 1 mm)等 [57] . 虽 然 In-cell NMR 近年来有较大的发展, 但在所有报道的 液体 in-cell NMR 研究中, 其中目的蛋白质的 NMR 线宽 kDa 的蛋白质, 绝大部分蛋白质, 包括很多分子量同样 小于 10 kDa 的蛋白质不能用传统的核磁共振方法获得 高分辨谱 [49,50,58,59] . In-cell NMR 目前还处于起步阶段, 需要大力发展新的标记方法, 脉冲序列和快速采样及信 号处理方法以克服灵敏度低和背景信号干扰等问题.…”
Section: In-cell Nmrunclassified